Reduced-scale model study on cable heat dissipation and airflow distribution of power cabins. (September 2019) - Wang, Jiaxu; Liu, Xuefeng; Chen, Siwei; Jiang, Hanghang; Fang, Guanyu; Chen, Wenjing; Deng, Shiming
Highlights: A reduced-scale model of power cabin and cable was verified. Effect of ventilation, ampacity and position on cable temperature was analyzed. Airflow distribution bring a temperature difference between the cables at 2.86 °C. The turbulence causes the cable to produce a temperature drop of 6.5 °C. The cooling effect after the wind speed exceeds a certain value is very limited. Abstract: The current work study the heat dissipation characteristics and airflow distribution in a power cabin. By simplifying the cable structure, a 1:5 reduced-scale model was constructed based on the Archimedes number. Computational fluid dynamics (CFD) simulations were applied to the prototype power cabin. The 3D steady-state Reynolds average Navier-Stokes (RANS) equation is used to solve the ventilation flow, where the turbulence model is realizable k–ε. The CFD simulation of the prototype has been verified by the reduced-scale model. On this basis, several conclusions were drawn. The airflow distribution in the power cabin and cable arrangement cause a difference in the temperature distribution between the cables. The strong turbulence at the air inlet causes a significant temperature drop. The mechanical fan can effectively cool the cable to a certain extent, but cable temperature control should take into account the effects of ampacity and ventilation, as well as cable location.